Expression of CK8 and CK17, specific epithelial markers, by oral squamous cell carcinoma cell lines - Mashhadiabbas, Fatemeh; Shavakhi, Mozhgan; Nazarian, Hamid; Kardouni Khoozestani, Parisa; Moslemi, Hamidreza (Journal of Dental School, 2019)
Objectives Oral squamous cell carcinoma (OSCC) is among the most common cancers worldwide. This study aimed to assess the expression of CK8 and CK17 by OSCC cell lines in Iranian patients. Methods This observational study was conducted on three OSCC cell lines with a minimum of 45 passages. Cells isolated from three patients with OSCC were cultured and passaged. Expression of CK8 and CK17 epithelial markers was assessed using reverse-transcription polymerase chain reaction. Data were presented qualitatively. Results The results confirmed the expression of CK8 and CK17 mRNA in three groups. Expression of these markers was different in the three specimens based on their degree of malignancy. Conclusion Since CK8 and CK17 were expressed in different superficial and basal layers in the three specimens, epithelial origin of these cells was confirmed. This study can pave the way for further cancer research and designing new treatments